2008
DOI: 10.1111/j.1468-0106.2008.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Property Market and the Macroeconomy of Mainland China: A Cross Region Study

Abstract: This paper studies the nexus between the property market and macroeconomy of China in 1998-2004, using panel data models covering 31 provinces and major cities. The estimates suggest three main conclusions. First, there seemed to be a two-way linkage between property prices and GDP growth. Second, bank credit expansion did not seem to play an 'accelerating' role in property price inflation, although the latter is found to have contributed to bank credit increases in recent years. Third, property price growth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 22 publications
(21 reference statements)
3
24
0
Order By: Relevance
“…This perception increases financial institutions' risk-taking capacity and their willingness to extend credit, so they pour more loans into the economy. Supporting empirical research of such a cause and effect link from house prices to credit volume includes studies by Gerlach and Peng (2005) and Peng et al (2008) …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This perception increases financial institutions' risk-taking capacity and their willingness to extend credit, so they pour more loans into the economy. Supporting empirical research of such a cause and effect link from house prices to credit volume includes studies by Gerlach and Peng (2005) and Peng et al (2008) …”
Section: Literature Reviewmentioning
confidence: 99%
“…Their cointegration analysis suggests that the property prices in Hong Kong are weakly exogenous, and the causality goes from property prices to bank loans. Peng et al (2008) investigate the relationship between the property market and the macroeconomy in mainland China from 1998 15 PM 2.5 measures the number of tiny particles with diameters less than 2.5 micrometers. Such particulate matters can enter deep into human lungs and cause potential cardiovascular and respiratory diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of housing wealth can promote household consumption, which also contributes to economic growth (Edelstein and Lum 2004). However, Peng et al (2008) pointed out that there was a lack of wealth effect on consumption in China, mainly owing to the limited means to withdraw housing equity to finance current consumption. This is shared by Ouyang (2011) who pointed out that, due to the housing affordability crisis, many people in China reduce entertainment spend and careful calculation in daily expenditure in order to set aside money for down payment or mortgage payment.…”
Section: Effect On Economic Developmentmentioning
confidence: 99%
“…Hongyu et al (2002) found that the growth of housing investment in China contributed to GDP growth in the short run. Also, Peng et al (2008) and Chen et al (2011) found that property price inflation brought about real GDP growth in China mainly through the investment channel. However, Jin-hai (2009) have shown that overheated investment would result in unbalanced economics structure (Jin-hai 2009), and hence gave rise to instability of housing market, which will eventually affect the economic development (Clapham 1996;Beltratti and Morana 2010).…”
Section: Effect On Economic Developmentmentioning
confidence: 99%